INDONESIAN EFL NON-ENGLISH MAJOR STUDENTS’ MOTIVATION TO USE AI IN WRITING - Silalahi, Rentauli (Journal of English Educational Study (JEES), 2025)
This study investigates the motivations of Indonesian non-English major EFL freshmen students in using Artificial Intelligence (AI) for writing. While the role of AI in academic contexts has been widely studied, most research has focused on English department students, leaving a gap in understanding how students outside these departments engage with AI tools for writing. Using a mixed-methods approach, this study combines a closed-ended survey with semi-structured interviews to explore students' motivation to adopt AI in their writing practices. Grounded in the Technology Acceptance Model, this study surveyed 40 freshmen students and conducted interviews with five selected through convenience sampling. The findings suggest that students primarily adopt AI for its perceived ease of use and its ability to assist with common writing challenges, such as grammar, vocabulary, and sentence structure. However, some students reported difficulties with AI’s accuracy and the need for more effective prompting techniques. Despite the benefits, the study also highlights concerns about students’ growing dependence on AI, potentially hindering their development of independent writing skills. These findings contribute to the ongoing discourse on AI integration in language learning and offer implications for educators and curriculum developers in supporting students’ use of AI while fostering critical writing skills. Future research should explore long-term effects and strategies to mitigate overdependence on AI tools.